Forensic analysis on discord application using the National Institute of Standards and Technology (NIST) Method - Muhammad Koprawi; Fadhli Dzil Ikram (Jurnal Mandiri IT, 2023)
Discord has shut down 30,000 communities due to various violations. In addressing the misuse of the Discord application, particularly in the form of sexual harassment, the problem of how to retrieve deleted messages from Discord desktop conversations using the National Institute of Standards and Technology (NIST) SP 800-86 method can be addressed. The NIST (National Institute of Standards and Technology) SP 800-86 method is employed for conducting digital evidence analysis or the process of obtaining information from digital evidence. The stages of the NIST method are Collection, Examination, Analysis, and Reporting. The accuracy level of the files obtained using the FTK Imager application is 16.67%, with the variables being evidence of image files. On the other hand, the ChromeCacheView application achieves 73.33% accuracy with variables including evidence of image files, videos, text messages, accounts, and emails. However, not all text messages are retrieved by ChromeCacheView. Autopsy, with a score of 33.33%, manages to retrieve images and emails.